Implementation of a robust cruise control using look-ahead method. Issue 11 (2016) - Gáspár, Péter; Németh, Balázs; Basset, Michel; Orjuela, Rodolfo
Abstract: The paper proposes the implementation of a robust cruise control system which is able to ensure the fuel-efficient travel of the vehicle with a look-ahead control algorithm. The H ∞ -based feedforward-feedback control method guarantees robustness against varying vehicle mass, longitudinal disturbances and the consideration of actuator dynamics. The advantage of the method is the application of a small number of vehicle parameters. Therefore, a method for various passenger cars without significant modifications is needed. The proposed cruise control and the look-ahead method are implemented in a software-in-the-loop (SIL) environment using DSpace Autobox, which cooperates with the high-fidelity CarSim software through CAN communication.